Diagnostic challenges of neurosarcoidosis in non-endemic areas - Shrestha, Keshari; Kleinschmidt-DeMasters, B. K.; Ormond, D. Ryan (Frontiers in Neurology, 2024)
Background: Neurosarcoidosis (NS) is a challenging diagnosis, particularly when cases occur in low-prevalence, non-endemic geographic regions. In the United States, the highest incidence is in the Midwest and Northeast, compared to our Southwest location. While it is well-known that NS may clinically and neuroradiographically mimic meningeal carcinomatosis, autoimmune or infectious pachymeningitis, neurosyphilis, or tuberculosis, diagnosis may be particularly challenging if systemic signs of sarcoidosis are lacking or unconfirmed or if dural-based masses are present. We reviewed our Colorado experience with NS cases, focusing our study on cases where NS represented the first histological confirmation of disease. Methods: Search of departmental databases via a text word for "neurosarcoidosis", 1-2008 to 12-2019, inclusive. Patients were only included if they had unusual clinical and neuroimaging features and only when central nervous system (CNS) biopsy represented the first confirmed diagnosis of sarcoidosis.Results: Seventeen total cases were identified, 9 of which the CNS biopsy was first confirmation of disease. The most unusual were 2 patients with dural-based masses, one of which had pure NS as the cause of meningioma-like lesions and the second of which had coexistent meningioma and intimately admixed non-necrotizing granulomas of NS.Conclusions: NS with unusual features, especially in non-endemic areas, continues to yield diagnosis challenges for neurologists, neuroradiologists, and pathologists.